2006
DOI: 10.1210/en.2005-1324
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Spontaneous Contractile Activity in the Bovine Epididymal Duct by Cyclic Guanosine 5′-Monophosphate-Dependent Pathways

Abstract: Passage of spermatozoa through the epididymis is obligatory for sperm maturation processes and is based on spontaneous phasic contractions (SC) of the epididymal duct. Here, the functional role of cyclic GMP (cGMP) signaling in modulating SC in the bovine epididymal caput and corpus region was examined by muscle tension recording and immunological and autoradiographic techniques. The cGMP-analog 8-bromo (Br)-cGMP, as well as the nitric oxide (NO) donor sodium nitroprusside and the natriuretic peptides (NPs) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 62 publications
8
34
0
4
Order By: Relevance
“…These results agree with those reported in the cat, dog, guinea pig and human (El Badawi and Schenk, 1967;Norberg et al, 1967;Baumgarten et al, 1968;Hodson et al, 1970;Dail et al, 1993;Gürtler, 2001) including camelus dromedarius (Saleh et al, 2002). The smooth musculature of the caput and corpus epididymis displays spontanueous contraction involving cGMP in the signalling pathway (Risley, 1958;Talo, 1981;Gerendai et al, 2001;Mewe et al, 2006), while the cauda epididymis is normally quiescent until neural input is received during the ejaculatory process (Hib et al, 1982). The localization of Liguori et al cathecolaminergic fibres within the epididymis in peritubular and subepithelial regions suggests that cathecolamines play a role in neuromuscular events required for the transport of spermatozoa through the duct and for seminal emission.…”
Section: Resultssupporting
confidence: 88%
“…These results agree with those reported in the cat, dog, guinea pig and human (El Badawi and Schenk, 1967;Norberg et al, 1967;Baumgarten et al, 1968;Hodson et al, 1970;Dail et al, 1993;Gürtler, 2001) including camelus dromedarius (Saleh et al, 2002). The smooth musculature of the caput and corpus epididymis displays spontanueous contraction involving cGMP in the signalling pathway (Risley, 1958;Talo, 1981;Gerendai et al, 2001;Mewe et al, 2006), while the cauda epididymis is normally quiescent until neural input is received during the ejaculatory process (Hib et al, 1982). The localization of Liguori et al cathecolaminergic fibres within the epididymis in peritubular and subepithelial regions suggests that cathecolamines play a role in neuromuscular events required for the transport of spermatozoa through the duct and for seminal emission.…”
Section: Resultssupporting
confidence: 88%
“…The findings are consistent with and support previously reported roles for NPs in the regulation of spontaneous contractility in smooth muscle cells lining the epididymal duct (Mewe et al 2006). An apparent predominance of GC-B versus GC-A was confirmed by membrane GC assays, where CNP elicited threefold higher amounts of cGMP than ANP.…”
Section: Organ-specific Characteristics Of Cgmp Signalingsupporting
confidence: 93%
“…An apparent predominance of GC-B versus GC-A was confirmed by membrane GC assays, where CNP elicited threefold higher amounts of cGMP than ANP. The data probably explain at a molecular level the higher efficacy of CNP (compared with ANP) in reducing the frequency of spontaneous phasic contractions and affecting the muscle tone in bovine epididymal ducts (Mewe et al 2006). In addition to these activities operating in the control of sperm movement, recent findings elucidated a pivotal role for cGMP signaling in the epididymal epithelium, serving to regulate proton secretion into the lumen (Shum et al 2008).…”
Section: Organ-specific Characteristics Of Cgmp Signalingmentioning
confidence: 95%
See 1 more Smart Citation
“…13 Transcripts of PDE10 were found in the human testis, 14 cGMP-hydrolyzing PDE5 was localized in peritubular myoid cells of rats 15 and regulation of epididymal duct contractility by PDE3 has been suggested. 16 PDE11, the latest isoform of the PDE family that raised interest recently, 17 contains one gene, PDE11A, with four splice variants (PDE11A1-4). It was suggested that PDE11A3 is found in the testis, whereas PDE11A4 is found in the prostate.…”
Section: Introductionmentioning
confidence: 99%